How well are we controlling falls from height in construction? Experiences of union carpenters in Washington State, 1989–2008. Issue 1 (22nd August 2013) - Lipscomb, Hester J.; Schoenfisch, Ashley L.; Cameron, Wilfrid; Kucera, Kristen L.; Adams, Darrin; Silverstein, Barbara A.
Abstract Background Falls from height (FFH) continue to cause significant morbidity and mortality across the construction industry. Methods By linking data on work hours with workers' compensation records, rates of work‐related injuries resulting from FFH and associated days away from work were evaluated among a large cohort (n = 24, 830) of union carpenters in Washington State from 1989 to 2008. Using Poisson regression we assessed rates of FFH over the 20‐year period while adjusting for temporal trend in other work‐related injuries. Patterns of paid lost days (PLDs) were assessed with negative binomial regression. Results Crude rates of FFH decreased 82% over the 20‐year period. Reductions were more modest and without demonstrable change since 1996 when adjusting for the temporal reduction in other injuries. Younger workers had higher injury rates; older workers lost more days following falls. Rates of PLDs associated with falls decreased over time, but there was not a consistent decline in mean lost days per fall. Conclusion These patterns are consistent with decreased FFH for several years surrounding state (1991) and then federal (1994) fall standards; the decline during this time period exceeded those seen in injury rates overall in this cohort. While crude rates of FFH have continued to decline, the decline is not as substantial as that seen for other types of injuries. This could reflect a variety of things including more global efforts designed to control risk (site planning, safety accountability) and changes in reporting practices. Am. J. Ind. Med. 57:69–77, 2014. © 2013 Wiley Periodicals, Inc.